An??lise de impacto do Fies sobre a renda do trabalhador formal - Rocha, Wilsimara Maciel (2016)
This paper aims to evaluate the effect of the major Student Loan Program of the Federal Government in Brazil, called Fies, on workers??? income in one side and on access to high education. The database used are the Rela????o Anual de Informa????es Sociais ??? RAIS identified by the social security number in 2003 and 2013 and individual - Ministry of Employment and Social Security and beneficiaries of Fies that started and finished high education between 2004 and 2012 and those data came from National Fund for Development of Education ??? FNDE. The methodology applied is the Propensity Score Matching ??? PSM which in this case compares two groups: beneficiaries of Fies, called treated group; and formal workers that were not benefited by Fies, however they have very similar characteristics to those that were. These workers are the controlled group. The results from logistic regression show that likelihood to use Fies increases if the workers have finished high school, are working in specific sectors of activities such as Transformation Industry, Extractive Industry, Construction, Trade, Services and are living in the Northeast region. Contrary, the likelihood to use Fies decreases if the workers are white, living in the Southeast, South or Midwest region and are older. The average treatment effect on treated (ATT) is positive, indicating that Fies contributes to increase workers??? income in around 20% and it has also contributed to increase access to high education. Finally, the T-test shows that distribution of covariates is balanced and the nearest neighbor matching was effective in getting the counterfactual very similar to the treated group.